H ( x ) = x 2 + 1 and K ( x ) = − x 2 + 4 .
What are the solutions to K ( H ( x ) ) = 0 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Very complicated answer IMHO. You just need to notice that K ( y ) = − ( y − 2 ) ( y + 2 ) then use y = H ( x ) which gives K ( H ( x ) ) = − ( x 2 + 1 − 2 ) ( x 2 + 1 + 2 ) K ( H ( x ) ) = − ( x 2 − 1 ) ( x 2 + 3 ) K ( H ( x ) ) = − ( x − 1 ) ( x + 1 ) ( x − i 3 ) ( x + i 3 ) hence the roots are ± 1 and ± i 3
Log in to reply
Hey can you tell me how to change the Background colour when you are writing the answer ?
I'd just factor after substitution after you get -(x^2 + 1)^2 + 4 = 0, multiply both sides by neg 1, you'll get a DOTS (difference of two squares)
K ( H ( x ) ) = 0 − H ( x ) 2 + 4 = 0 4 = H ( x ) 2 H ( x ) = ± 2 x 2 + 1 = ± 2
If x 2 + 1 = 2 , then
x 2 = 1 x = ± 1
and if x 2 + 1 = − 2 , then
x 2 = − 3 x = ± 3 i
The solutions are x = ± 3 i or x = ± 1
Nicely presented solution
This is an incredibly elegant solution.
Nicely written.
-(x^2 + 1)^2 + 4 = 0
=> (x^2 + 1)^2 - 2^2 = 0
=> (x^2 + 1 - 2)(x^2 + 1 + 2) = 0
=> (x^2 - 1)(x^2 + 3) = 0
=> x = +/- 1 OR x = +/- j sqrt(3)
K ( H ( x ) ) = − ( x 2 + 1 ) 2 + 4
K ( H ( x ) ) = − x 4 − 2 x 2 − 1 + 4
K ( H ( x ) ) = − x 4 − 2 x 2 + 3
0 = − x 4 − 2 x 2 + 3
0 = ( − x 2 − 3 ) ( x 2 − 1 )
− x 2 − 3 = 0 → x 2 = − 3 → x = ± 3 i
x 2 − 1 = 0 → x 2 = 1 → x = ± 1
x = ± 1 , ± 3 i
Say: y = H ( x ) = x 2 + 1
= > K ( H ( x ) ) = K ( y ) = − y 2 + 4 = 0
= > y = ± 2
= > x 2 + 1 = ± 2
= > x = ± 1 or x = ± i 3
H(x) = x^2 + 1; K(x) = - x^2 + 4;
K(H(x)) = - (x^2 + 1)^2 + 4 = 0;
suppose: x^2 + 1 = t, so:
- t^2 + 4 = 0, t^2 = 4; => t1 = + 2; t2 = - 2;
1) x^2 + 1 = 2, x^2 = 1; => x1 = + 1; x2 = - 1;
2) x^2 + 1 = - 2, x^2 = - 3; => x3 = + i
sqrt(3); x4 = - i
sqrt(3);
Note: next time i will try to use an equation editor.
K ( H ( x ) ) = K ( x 2 + 1 ) = − ( x 2 + 1 ) 2 + 4
N o w K ( H ( x ) ) = 0 ⇒ − ( x 2 + 1 ) 2 + 4 = 0 S o ( x 2 + 1 ) 2 − 4 = 0 [ M u l t i p l y i n g e a c h s i d e b y − 1 ] ( x 2 + 1 ) 2 − 2 2 = 0 ( x 2 + 1 − 2 ) ∗ ( x 2 + 1 + 2 ) = 0 [ a 2 − b 2 = ( a + b ) ( a − b ) ] ( x 2 − 1 ) ∗ ( x 2 + 3 ) = 0
H e n c e E i t h e r ( x 2 − 1 ) = 0 o r ( x 2 + 3 ) = 0 i f ( x 2 − 1 ) = 0 ( x + 1 ) ∗ ( x − 1 ) = 0
H e n c e ( x + 1 ) = 0 o r ( x − 1 ) = 0 i . e x = − 1 o r x = + 1 [ s o l u t i o n 1 x = ± 1 ]
i f ( x 2 + 3 ) = 0 i . e ( 1 ) x 2 + ( 0 ) x + ( 3 ) = 0 b y q u a d r a t i c s o l v i n g f o r m u l a [ x = 2 a − b ± 2 b 2 − 4 a c ] a = 1 , b = 0 , c = 3 x = 2 ∗ 1 − 0 ± 2 0 − 4 ∗ 1 ∗ 3 ⇒ x = 2 ± − 1 2 = ± i 3 [ s o l u t i o n 2 x = ± i 3 ] H e n c e t h e s o l u t i o n s a r e x = ± 1 , ± i 3
Your solution is nice.
Problem Loading...
Note Loading...
Set Loading...
K ( H ( x ) )
= K ( x 2 + 1 )
= − ( x 2 + 1 ) 2 + 4
= − ( x 4 + 2 x 2 + 1 ) + 4
= − x 4 − 2 x 2 + 3
So solve for x 2 using the quadratic formula gives:
x 2 = − 2 − ( − 2 ) ± 4 + 1 2
= − 2 2 ± 4
= − 1 ± 2 = 1 , − 3
So x 2 = 1 o r − 3 thus x = ± 1 o r ± 3 i